Why is - multiplied by - = +? Plz explain both by algebraic and co-ordinate system.

Asked by mmishra23 | 29th Apr, 2009, 05:22: PM

Expert Answer:

In the method you gave n(-1)(-1)=(1/n)(-1) = n
It should have been (n-1)-1 = (1/n)-1 = n  which leads to prove that reciprocal of reciprocal is number itself

Here is a method to prove algebraically

Basically we need to find
(-1)(-1) = ?

The possible values could be -1 or +1

and the answer is that the following convention has been adopted:

(-1)(-1) = +1

For example, if we adopted the convention that (-1)(-1) = -1, the distributive property of multiplication wouldn't work for negative numbers:

(-1)(1 + -1) = (-1)(1) + (-1)(-1)

(-1)(0) = -1 + -1

0 = -2
Which is contradiction hence(-1)(-1) = +1

Answered by  | 5th May, 2009, 04:04: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.